Patient involvement in the encounter between general practice and patients with a chronic disease. Results of a scoping review focusing on type 2 diabetes and obstructive pulmonary disease - Signe Beck Titlestad; Michael Marcussen; Marie Sandstød Rasmussen; Birgitte Nørgaard (European Journal of General Practice, 2022)
AbstractIntroduction Research has shown improved health outcomes when patients are involved in managing their health conditions and when their individual needs are considered.Objectives This scoping review aimed to map the existing research regarding chronic disease patients’ involvement in their encounters with general practice, with a specific focus on patients with Type 2 diabetes (TD2) or chronic obstructive pulmonary disease (COPD) and from the perspectives of both general practitioners and patients.Methods Studies of any design, date, and language were included. A systematic search was conducted using the following databases: Medline, CINAHL, PsycInfo, Scopus, and EMBASE from August until October 2020 and renewed September 2021. Data were systematically charted by the following study characteristics: bibliographic aims; study aims; setting; area of interest; results; conclusion.Results Eighteen studies were included; they conducted qualitative methods, surveys or mixed methods. From the patients’ perspectives, the importance of being more involved in treatment discussions during consultations as well as a friendly environment, was underscored. A good relationship and relational continuity make it easier for patients to be more involved in treatment decisions. From the general practitioner (GP) perspectives, they mentioned their high workload, long-standing relationships, knowledge about the patients and prepared patients as factors influencing their ability to involve patients in treatment discussions.Conclusion A good GP–patient relationship was considered an important aspect to providing and facilitating for involvement of patients with COPD or TD2. Scoping review registration: https://osf.io/ynqt2